The Complementary Roles of Qur'an Education Center and Elementary Schools in Strengthening Islamic Religious Education - Salamat, Nabilah Safira; Fakhruddin, Agus; Firmansyah, Mokh. Iman; Muflih, Abdillah (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2026)
Islamic Religious Education (PAI) in elementary schools faces a specific problem: learning is predominantly cognitive and classroom-based, resulting in weak habituation and limited translation of religious knowledge into daily behavior. Existing studies broadly examine PAI within formal schooling or analyze Qur'an-based non-formal institutions (TPA) independently, leaving a gap in understanding how TPA functions as a complementary institution that holistically strengthens PAI learning. This study aims to analyze the complementary contribution of TPA to elementary PAI learning outcomes across cognitive, psychomotor, and affective domains. A descriptive qualitative methodology was employed using an analytical framework grounded in the three core domains of PAI. Data were collected through triangulation of documents, semi-structured interviews, and observations involving 17 participants, including TPA administrators, teachers, elementary PAI teachers, and students active in both institutions. The findings reveal three analytical patterns: (1) cognitively, TPA reinforces conceptual understanding through memorization repetition, tajwid mastery, and enrichment of Qur'an, aqidah, fiqh, akhlak, and Islamic history; (2) psychomotorically, TPA strengthens religious skills through systematic worship practices and experiential activities; and (3) affectively, TPA cultivates religious attitudes and character through structured habituation and teacher modeling. This study contributes to PAI scholarship by conceptualizing TPA as a strategic complementary institution that bridges the gap between religious knowledge and lived religious practice.